Securing the Global City: Crime, Consulting, Risk, and Ratings in the Production of Urban Space - Beckett, Katherine (2008)
The last decade has witnessed the rise of private transnational institutions that increasingly influence the organization and management of urban space. Two institutions are especially powerful in this regard: bond-rating agencies and global security firms. Bolstered by a discourse of risk and the need to securitize cities, these institutions have garnered enormous amounts of power with respect to urban social and spatial control. They are implicated in the imprisonment and displacement of marginalized populations, the intensification of gentrification, and general shifts in municipal funding priorities. The authors illustrate these themes through a case study of New York City, followed by an example of the transnational movement of these forces and their exportation to sites such as Mexico City. Democracy and the Transnational Private Sector, Symposium. Indiana University School of Law – Bloomington, April 12-13, 2007